Patient-specific 3D Printing: A Novel Technique for Complex Pediatric Renal Transplantation. Issue 2 (February 2019) - Chandak, Pankaj; Byrne, Nicholas; Coleman, Andrew; Karunanithy, Narayan; Carmichael, Jim; Marks, Stephen D.; Stojanovic, Jelena; Kessaris, Nicos; Mamode, Nizam
Abstract : Objective: The authors investigated a novel application of patient-specific three-dimensional (3D) printing, to enhance preoperative, multidisciplinary planning in complex, living-donor pediatric renal transplantation. Summary Background Data: For children with end-stage kidney disease, the transplantation of adult-sized, living-donor kidneys into small recipients (<20 kg) with increasingly complex structural anomalies can be difficult. Establishing the operative feasibility in such cases demands a surgical understanding of anatomy to be derived from medical imaging. However, this is hampered by the representation of complex structures in 2D, the inherent interpretive expertise this demands, and the challenge of conveying this appreciation to others. Methods: We report the novel use of patient-specific 3D printed models to achieve personalized management for 3 children who underwent living-donor renal transplantation. Each presented a unique surgical challenge that would otherwise prevent preoperative determination of transplantation feasibility. Patient-specific geometries were segmented from imaging data and fabricated using polyjet, 3D printing technology. Models were verified by an expert radiologist and presented during multidisciplinary discussion and surgical simulation. Results: 3D printed models enhanced preoperative deliberation and surgical simulation and allowed on-table exploration of a small child to be avoided. We have critically determined specific clinical indications, technical insights, limitations, and outcomes of this approach. At latest follow-up (>16 mo) all patients remain well with functioning renal allografts. Conclusions: We report the new and safe integration of patient-specific 3D printing into complex pediatric renal transplantation. This technique enhances surgical planning and can inform operative feasibility in those cases which would otherwise be uncertain.